2012
DOI: 10.1038/ajg.2012.167
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Endoscopy, Advanced Adenomas, and Sessile Serrated Polyps: Implications for Proximal Colon Cancer

Abstract: OBJECTIVES Colonoscopy is associated with a decreased risk of colorectal cancer but may be more effective in reducing the risk of distal than proximal malignancies. To gain insight into the differences between proximal and distal colon endoscopic performance, we conducted a case-control study of advanced adenomas, the primary targets of colorectal endoscopy screening, and sessile serrated polyps (SSPs), newly recognized precursor lesions for a colorectal cancer subset that occurs most often in the proximal col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 53 publications
0
31
0
Order By: Relevance
“…Among screening methods colonoscopy remains the best technics to detect the high risk patients. study on 213 advanced adenomas and 172 sessile serrated polyps(SSP) patients In 2012 revealed that previous endoscopy had a significant decrease in development of advanced adenoma in both the rectum/ distal colon and proximal colon but their findings wasn't significant in SSps cases (Burnett-Hartman et al, 2012) Most of the polyps in our study located in rectosigmoid (63.1%). This is similar to study of Bafandeh et al (2008), Mirzaie et al (2012) and Hodadoostan et al (2010) in which they found rectum and sigmoid together the most common site of the lesions in Iranian patients with colon polyps.…”
Section: Discussionmentioning
confidence: 82%
“…Among screening methods colonoscopy remains the best technics to detect the high risk patients. study on 213 advanced adenomas and 172 sessile serrated polyps(SSP) patients In 2012 revealed that previous endoscopy had a significant decrease in development of advanced adenoma in both the rectum/ distal colon and proximal colon but their findings wasn't significant in SSps cases (Burnett-Hartman et al, 2012) Most of the polyps in our study located in rectosigmoid (63.1%). This is similar to study of Bafandeh et al (2008), Mirzaie et al (2012) and Hodadoostan et al (2010) in which they found rectum and sigmoid together the most common site of the lesions in Iranian patients with colon polyps.…”
Section: Discussionmentioning
confidence: 82%
“…A recent study found that colonoscopy conferred a statistically significant reduction in the future risk of proximal advanced adenomas, but not proximal sessile serrated polyps. 27 It is unclear whether inadequate colonic preparation in the proximal colon might have played a role in this finding. To date, there have been little data in the medical literature regarding ADR and SDR in the proximal colon of patients with inadequate or suboptimal preparations, leading to our current investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, fecal blood tests fail entirely to detect the subset of sessile serrated polyps [4,43], lesions which are also often missed by colonoscopy and may help to explain its lesser effect on proximal disease [58].…”
Section: Interval Testing Between Screening Colonoscopy?mentioning
confidence: 99%